Measurement confounding affects the extent to which verbal IQ explains social gradients in mortality. Issue 8 (11th April 2014) - Chapman, Benjamin; Fiscella, Kevin; Duberstein, Paul; Kawachi, Ichiro; Muennig, Peter
Abstract : Background: IQ is thought to explain social gradients in mortality. IQ scores are based roughly equally on Verbal IQ (VIQ) and Performance IQ tests. VIQ tests, however, are suspected to confound true verbal ability with socioeconomic status (SES), raising the possibility that associations between SES and IQ scores might be overestimated. We examined, first, whether two of the most common types of VIQ tests exhibited differential item functioning (DIF) favouring persons of higher SES and/or majority race/ethnicity. Second, we assessed what impact, if any, this had on estimates of the extent to which VIQ explains social gradients in mortality. Methods: Data from the General Social Survey-National Death Index cohort, a US population representative dataset, was used. Item response theory models queried social-factor DIF on the Thorndike Verbal Intelligence Scale and Wechsler Adult Intelligence Scales, Revised Similarities test. Cox models examined mortality associations among SES and VIQ scores corrected and uncorrected for DIF. Results: When uncorrected for DIF, VIQ was correlated with income, education, occupational prestige and race, with correlation coefficients ranging between |0.12| and |0.43|. After correcting for DIF, correlations ranged from |0.06| to |0.16|. Uncorrected VIQ scores explained 11–40% of the Relative Index of Inequalities in mortality for social factors, while DIF-corrected scores explained 2–29%. Conclusions: Two of the common forms of VIQ tests appear confound verbal intelligence with SES. Since these tests appear in most IQ batteries, circumspection may be warranted in estimating the amount of social inequalities in mortality attributable to IQ.